[Ag]2[B12Cl12] as a Catalyst in PhICl2 Mediated Chlorination. Issue 19 (22nd May 2021) - Poynder, Tiffany B.; Houston, Sevan D.; Dutton, Jason L.
Abstract: The weakly coordinating dianion [B12 Cl12 ] 2− originates from a family of carboranes typically reserved for application in coordination chemistry. Herein, we show that its readily accessible Ag(I) salt, [Ag]2 [B12 Cl12 ], can be used as a catalyst in the PhICl2 mediated chlorination of arenes, alkenes, and alkynes. The promising activity displayed by [Ag]2 [B12 Cl12 ] over a variety of commercially available Ag(I) sources merits its incorporation to the toolkit of commonly screened silver catalysts in synthesis. Abstract : The weakly coordinating dianion B12 Cl12 2− is typically associated with inorganic and superacid chemistry. Herein, we demonstrate the ability of its silver salt, [Ag]2 [B12 Cl12 ], to activate iodobenzene dichloride towards the chlorination of arenes, and dichlorination of alkenes/alkynes. [Ag]2 [B12 Cl12 ] outperformed a variety of commonly used Ag(I) sources, highlighting its potential for wider application throughout organic synthesis.